Effect of Leaflets and Balanced Menu Videos on Knowledge, Attitudes and Behaviors among Undernourished Toddlers’ Mothers - Maftuchah, Maftuchah; Setyaningsih, Faridha; Nurhayati, Susi (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: Toddlers are a vulnerable group in terms of nutrition and are at a high risk for disease. Toddlers’ nutritional health might be affected by a lack of nutrient intake. The nutritional status of children under the age of five is critical since it is an indicator of their health and nutritional status. Malnutrition continues to increase in Sukodono where there are currently 54 undernourished toddlers. This is due to the mother’s lack of knowledge. Counseling through leaflets and video screenings is one of the media for increasing mothers’ knowledge. This study aimed to analyzed the effect of leaflets and balanced menu videos on the knowledge, attitudes and behavior of malnourished mothers under five in the village of Sukodono Tahunan Jepara, Central Java.Methods: A quantitative research with quasi-experimental approach. The populations of the study were 54 undernourished toddlers at the aged 1 to 5 years. A total of 32 undernourished toddlers’ mothers in Sukodono were included in this study, and divided into 16 subjects from control group (using leaflet) and 16 subjects from intervention group (using video). Results: There was an effect of balanced menu leaflet media on the knowledge, attitudes, and behavior of malnourished toddler mothers in the village of Sukodono Tahunan Jepara. There is an effect of balanced menu video media on the knowledge, attitudes, and behavior of malnourished toddler mothers in Sukodono Tahunan village, Jepara. There is no more effective difference between giving leaflets and balanced menu videos on the knowledge, attitudes, and behavior of malnourished toddler mothers in Sukodono Tahunan Jepara village with p values > 0.05 (0.434, 0.067 and 0.131).Conclusion: There is no more effective difference between the provision of leaflets and balanced menu videos on the knowledge, attitudes, and behavior of undernourished toddlers’ mothers in Sukodono Tahunan Jepara with a p value > 0.05 (0.434, 0.067 and 0.131.